2020
DOI: 10.3390/agronomy10030318
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of Extra-Early Maturing Landraces for Improving Tolerance to Drought, Heat, and Both Combined Stresses in Maize

Abstract: Maize landrace accessions constitute an invaluable gene pool of unexplored alleles that can be harnessed to mitigate the challenges of the narrowing genetic base, declined genetic gains, and reduced resilience to abiotic stress in modern varieties developed from repeated recycling of few superior breeding lines. The objective of this study was to identify extra-early maize landraces that express tolerance to drought and/or heat stress and maintain high grain yield (GY) with other desirable agronomic/morpho-phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 41 publications
5
30
2
1
Order By: Relevance
“…Therefore, the Burkinabe gene pool, having been grown and selected by farmers over many generations under warmer and drier conditions, could harbor novel and favorable alleles for improving maize for tolerance to drought and heat stresses. It is notable that in our earlier work on this maize panel, the high degree of tolerance of the Burkinabe landraces to drought, heat, and the combined heat and drought stresses was unrivalled [ 47 , 48 ]. The high genetic similarity observed between the Ghanaian and Togolese landraces was supported by their low F ST (0.14) and high Nm (2.63) values.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Burkinabe gene pool, having been grown and selected by farmers over many generations under warmer and drier conditions, could harbor novel and favorable alleles for improving maize for tolerance to drought and heat stresses. It is notable that in our earlier work on this maize panel, the high degree of tolerance of the Burkinabe landraces to drought, heat, and the combined heat and drought stresses was unrivalled [ 47 , 48 ]. The high genetic similarity observed between the Ghanaian and Togolese landraces was supported by their low F ST (0.14) and high Nm (2.63) values.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high night temperatures during pollination and grain filling reduce maize yield due to increased respiration and decreased rates of net dry matter accumulation [27], which might explain the lower ESY that was obtained for SD2, 3, and 4. It has been reported that temperatures during flowering and the early stages of grain filling for tropical lowland maize have an optimal threshold between 23 • C at night and 34 • C during the day [28]. It is therefore necessary to establish optimal sowing dates (windows) for specific locations in the tropics, where the ESY of the females and/or the SY of the males can be maximized depending on the case.…”
Section: Relationship Between Sowing Dates Growing Degree Days Flormentioning
confidence: 99%
“…Although maize is well adapted and substantially utilized in the savannas of SSA, the concurrent incidence of abiotic stresses such as drought and high temperature during flowering could reduce the photosynthetic rate, accelerate leaf senescence, induce kernel abortion and ultimately cause drastic yield losses [19,20]. The combination of the two stresses could lead to a grain yield loss of more than 90% during flowering and grain filling in maize [10,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%